Konsep dan Penerapan Takwil Muhammad Quraish Shihab dalam Tafsir Al-Mishbah - Dedi Junaedi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
The problem of ta’wīl  in Qur’anic studies is regarded as one of the controversial issues. It requires a holistic study on ta’wīl. Some scholars still criticized the takwil as a method of understanding of the Qur’an. Some qur’anic commentators who did not give their commentaries will say Allāhu a’lamu bi murādihi (It is only God who knows the meaning). However, another commentator did not agree with them. They then use ta’wīl. One of qur’anic scholars who used ta’wīl  is Muhammad Quraish Shihab. He is an Indonesian qur’anic commentator. One of his works is ‘Tafsir al-Mishbah’. It can be called as a remarkable work of tafsir. He used the different method of qur’anic interpretation. He has a deep linguistic approach and comprehensive understanding. He also uses an approach of tafsīr bi al-ra’yi  that also used the traditional source as well.